Kesulitan Kepala Sekolah dalam Pengelolaan Kurikulum 2013 pada Sekolah Dasar di Kecamatan Koto Tangah Kota Padang - Gina Mariani; Elizar Ramli (Jurnal Bahana Manajemen Pendidikan, 2020)
This article discusses the difficulties of the principal in managing the 2013 curriculum in elementary schools in Koto Tangah sub-district, Padang City in terms of: 1) curriculum planning, 2) curriculum implementation, 3) curriculum evaluation. The type of this research is descriptive research. The population of this study is the principal who is in Koto Tangah District Elementary School, Padang City, as many as 66 people. The number of samples is 25 people taken from the population using the Simple Random Sampling technique. Data collection tool is a questionnaire with a Likert Scale model that has been tested for validity and reliability. Data processing is done using the average formula (Mean). The results showed that the Principal Difficulties in the 2013 Curriculum Management at Elementary Schools in Koto Tangah Sub-District, Padang City on indicators: 1) 2013 curriculum planning gained an average score of 2.2 in the category of experiencing less difficulties, 2) the implementation of the 2013 curriculum gained scores 2.4 on average were in the category of having less difficulty, 3) the 2013 curriculum evaluation gained an average score of 2.7 in the category of having enough difficulties.